Optimalisasi Peran Keluarga, Sekolah, dan Masyarakat dalam Penguatan Pendidikan Karakter Berbasis Kearifan Lokal - Muhammad Mahmuda; Leli Syahputri; Adelia Puspita; Satria Wiguna (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This community service activity focuses on the "Optimization of the Roles of Family, School, and Community in Strengthening Character Education Based on Local Wisdom for Students of STAI Jam'iyah Mahmudiyah Langka." The activity aims to raise awareness and understanding of the importance of collaboration among families, schools, and the community in character education rooted in local wisdom. Through a series of discussion forums, workshops, and community service programs, all parties are encouraged to actively instill local wisdom values in students. The results of this activity indicate an increase in parental participation, the strengthening of relevant curricula in schools, and the involvement of students in local cultural activities. Furthermore, this initiative successfully created a strong synergy among various community elements, supporting the emergence of a generation of students who are not only knowledgeable but also possess strong character grounded in local culture. Thus, this service is expected to make a significant contribution to the development of character education within the STAI Jam'iyah Mahmudiyah Langka environment